Strategi Peningkatan Kinerja Guru - Mohamad Muspawi (Universitas Batanghari Jambi, 2021)
Teacher performance is an effort and the ability of teachers to carry out their duties and responsibilities at school during learning activities and can provide encouragement and influence to students with the aim that learning objectives can be achieved and run well and as expected which is shown in appearance, actions , and his work performance. Teacher performance is determined by four factors, namely: (1) environment; (2) individual characteristics; (3) organizational characteristics; and (4) job characteristics. Some of the efforts that the principal can make to improve teacher performance are: (1) Teacher performance guidance, (2) Supervision of teacher performance, (3). Providing motivation, (4). Evaluating teacher performance.